Application of proteomics to determine the mechanism of ozone on sweet cherries (Prunus avium L.) by time-series analysis - Zhao, Yuehan; Hou, Zhaohua; Zhang, Na; Ji, Haipeng; Dong, Chenghu; Yu, Jinze; Chen, Xueling; Chen, Cunkun; Guo, Honglian (Frontiers in Plant Science, 2023)
Ozone treatment could reduce the fruits softening induced adverse impacts on cherry. This study investigated the mechanism of ozone treatment on sweet cherry (Prunus avium L.) by Lable-free quantification proteomics and physiological traits. The results showed that a total of 4557 proteins were identified in all the samples, and 3149 proteins were common to all groups. Mfuzz analyses revealed 3149 candidate proteins. KEGG annotation and enrichment analysis showed proteins related to carbohydrate and energy metabolism and anthocyanin biosynthesis, cell stress response, and fruit firmness were characterized and quantified. The qRT-PCR results were in accordance with proteomics results which validated the conclusions. The present study for the first time reveals the mechanism of cherry in response to ozone treatment at a proteome level which is of importance for cherry storage.